Influence of commissioning arrangements on implementing and sustaining a complex healthcare intervention (ESCAPE-pain) for osteoarthritis: a qualitative case study. (December 2021) - Walker, Andrew; Boaz, Annette; Hurley, Michael V.
Abstract: Objectives: Funding in health care has a critical impact on the implementation and sustainability of evidence-based interventions. This study explored the perspectives of physiotherapists on the influence of commissioning arrangements on the implementation and sustainability of a group rehabilitation programme for osteoarthritis (ESCAPE-pain). Design: A qualitative case study approach using in-depth interviews. Setting: National Health Service (NHS) musculoskeletal (MSK) outpatient departments in England. Participants: Thirty physiotherapists in clinical and senior management roles from 11 NHS MSK providers. Results: Five themes were identified: (1) clinical perspectives of ESCAPE-pain – MSK services wanted to implement and sustain ESCAPE-pain because it provided evidence-based, quality care; (2) focusing on clinical activity over outcomes – commissioners were perceived as prioritising activity-based performance over delivering clinical outcomes; (3) rationing availability – patient access to ESCAPE-pain could be limited due to rationing resources; (4) absorbing costs – contracts did not always cover the activities associated with delivering ESCAPE-pain meaning that providers bore the costs; and (5) relationship between commissioners and providers – physiotherapists perceived a disconnect with commissioners and had little power to influence decisions. Conclusions: Commissioning arrangements for MSK physiotherapy services can impede providers from implementing and sustaining a clinically and cost-effective intervention. To be implemented and sustained, an intervention needs to integrate into clinical practice and the wider healthcare system. Commissioning arrangements for MSK physiotherapy need to allow providers the flexibility to deliver interventions that best meet the needs of their patients. The move to more strategic, integrated, outcome-based commissioning has the potential to facilitate the spread and sustainability of interventions.